Study of position and eruption of lower third molars in adolescents - Eduardo Machado Vilela; Paula Amorim Vitoi (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: The occurrence of retained lower third molars (3M) is common. A careful analysis is necessary for proper clinical management and the radiographic examination is fundamental. The use of panoramic radiographs is extremely important for the analysis and classification of 3M position, allowing the diagnosis and the establishment of the treatment planning for the removal of these teeth. Objective: The aim of this study was to evaluate the changes in position and eruption state of lower 3M during a period of 3.6 years, as well as to identify factors that may be related with early diagnosis of dental retention of these teeth in adolescent patients. Material and methods: One hundred and one initial (T1) and final (T2) panoramic radiographs from patients treating at the university’s orthodontic clinics were analyzed. The distribution of 195 lower 3Ms was evaluated taking into account personal data, collected from clinical records. The data obtained in relation to the positioning of the teeth were based on the ratings of Winter and Pell & Gregory. Results: The results showed that vertical position was the most prevalent and the C level and class II positions were predominant. The changes occurring in 3M position during the study interval were not statistically significant. Conclusion: After the final evaluation (T2) it was concluded that unpredictable changes in lower 3Ms position and eruption may occur. The variables race (P = 0.03) and anterior border of the mandibular ramus (P = 0.007) seem to have influence on the level of eruption, also suggesting influence on this tooth retention within dental arches over the years.